AFS@UFS: Academic facilitation in extended curricula in the Faculty of the Humanities - Naude, L; Bezuidenhout, MJ (South African Journal of Higher Education, 2016)
The Faculty of the Humanities at the University of the Free State launched an Academic Facilitation project to provide academic scaffolding to students in extended programmes. The aim of the facilitation sessions is to promote the integration of generic and language competencies with disciplinary content. The educational philosophy that guides the teaching-learning in this project incorporates the theories of experiential learning, social constructivism and cooperative learning. An action research approach with a mixed methods research design provides a research dimension to track the process and the impact of the project. Quantitative and qualitative data allude to the value of this project in facilitating access with success.